Developing preschool teachers' belief scale regarding educational technologies: A validity and reliability study - BALABAN DAĞAL, ASUDE; KANBUROĞLU, VOLKAN; UYANIK, GÜLDEN (My University, 2022)
In this study, it is aimed to develop a measurement tool that helps to determine preschool teachers’beliefs on educational technologies. An item pool of 100 items was created by examining field studies. 376 volunteer preschool teachers participated in the study. Exploratory factor analysis was performed on the list of questions which was reduced to 79 items as a result of the Lawshe analysis conducted within the scope of content validity. In the factor analysis, 79 variables were subjected to factor analysis, and 5 factors with an eigenvalue of 1 and above emerged as a result of varimax orthogonal rotation. These 5 factors explain 57.17% of the total variance. The Kaiser-Meyer-Olkin criterion shows that the sample is sufficient for factor analysis (KMO= 0.935). As a result of Bartlett's test of sphericity (x2(595) = 6773.24, p<0.001) it was confirmed that there were suitable correlations between the variables for factor analysis. The factor loading values of the scale, which consists of 5 sub-dimensions, vary between .58 and .78. After the factor structure of the scale was examined by exploratory factor analysis, a five-factor structure emerged. As a result of confirmatory factor analysis, it was found that this structure had a good level of modelfit (x2/sd=5.09, RMSEA= 0.10, SRMR= 0.06, GFI= 0.70, AGFI= 0.66, NFI=0.93, CFI=0.95, RFI=0.93). The internal consistency coefficient for the entire scale is .80. The internal consistency coefficients of the sub-dimensions were found as .90 for the Belief in the Contribution of Educational Technologies to Personal and Instructional Skills sub-dimension, .87 for the Belief in the Methodical Contribution of Educational Technologies sub-dimension, .85 for the Belief in the Positive Effects of Educational Technologies sub-dimension, .80 for the Negative Beliefs on the Use of Educational Technologies sub-dimension and .78 for the Belief in the Negative Effects of Educational Technologies sub-dimension. The analyzes showed that 35 item Preschool Teachers' Belief Scale on Educational Technologies is a valid and reliable scale
Keywords: Kindergarten teacher; Technology integration to education; Preschool education